Development and characterisation of recombinant LSDV-vectored dual vaccines against bovine leukaemia virus and lumpy skin disease virus - Suzuki, Akiko (Department of Pathology, 2020)
Bovine leukaemia virus (BLV) and lumpy skin disease virus (LSDV) are endemic to Africa and cause significant economic losses to the beef and dairy industries. Vaccines are the most cost-effective and efficient way to prevent infection and outbreaks. Currently, there is no commercially available vaccine against BLV. In contrast, there are several live attenuated vaccines against LSDV. A recombinant LSDV which could protect cattle against both LSDV and BLV would be of great benefit to the African continent. This Master’s degree project involved three objectives. Firstly, the genetic variabilities and phylogenetic relationships of eight South African BLV isolates with other BLV strains from different geographical regions worldwide with known genotypes were determined. The BLV full-length envelope (env) and gag genes were successfully sequenced from total DNA extracted from the blood of BLV-infected cattle from a single herd. The analyses indicated that the seven of the South African isolates characterised in this study belonged to genotype 4 and the eighth to genotype 1. Furthermore, amino acid substitutions in the BLV Env and Gag sequences unique to the South African isolates were identified. Secondly, the activity of five selected poxvirus promoters in cells infected with LSDV was assessed by the detection of transient expression of an enhanced green fluorescent protein (eGFP) reporter gene driven by the poxvirus promoters. The promoters tested were a modified early fowlpox virus promoter (pmFP), an early-late promoter of a 7.5 kilodalton polypeptide gene of vaccinia virus (VACV) (p7.5), a synthetic early-late promoter of VACV (pS), a modified early-late promoter of the H5 gene of VACV (pmH5) and a synthetic early-late optimised promoter of VACV (pLEO). The results showed that all the poxvirus promoters were functional in the LSDV-infected cells and the eGFP expression was stable over the 72-hour study period. Lastly, two LSDV-vectored dual vaccines containing BLV immunogen(s) were developed and characterised. The first recombinant LSDV-vectored vaccine contained the BLV Env and Gag immunogens and the second recombinant LSDV-vectored vaccine contained the BLV Env immunogen alone. The presence of the BLV env gene in the recombinant LSDV vaccine was confirmed by polymerase chain reaction (PCR) and the BLV env sequence was confirmed by Sanger sequencing. Furthermore, BLV Env and Gag protein expression were confirmed by immunofluorescent staining and Western blotting, respectively. Future work will involve further purification of the recombinant viruses, confirmation of the production of BLV Gag virus-like particles and the preparation of high titre stocks of the vaccines to test in cattle.